2004
DOI: 10.1111/j.1440-1592.2004.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet-inactivated herpes simplex virus type I on atopic dermatitis-like lesions in NC/Nga mice: Role of the suppressor of cytokine signaling in the skin

Abstract: Background:  Atopic dermatitis (AD) is characterized by repetitious eczematous skin and is Th2 dominant in nature. Atopic dermatitis lesions have been observed to improve in patients during viral or bacterial infection, such as herpes simplex virus (HSV). A Th1 pathway established to counter viral infection may possibly be the mechanism for the relief of skin lesions in AD. Methods:  In animal AD models using NC/Nga mice, the effects of local intra‐ and/or subcutaneous injection of ultraviolet inactivated‐HSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
6
2
Order By: Relevance
“…Weak SOCS3 expression might thus cause reduction in Th2, resulting in a requirement for involvement of Th1. In our recent report, 11 SOCS3 mRNA expression in lesional skin was reduced more in NC/Nga mice that had been administered ultraviolet‐inactivated herpes simplex virus; their skin lesions improved after virus administration. We believe therefore that SOCS3 reduction downregulates Th2 and thus expression and/or levels of SOCS3 might provide a specific indication of the severity and/or improvement of AD and the shift from Th2 to Th1 or vice versa .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Weak SOCS3 expression might thus cause reduction in Th2, resulting in a requirement for involvement of Th1. In our recent report, 11 SOCS3 mRNA expression in lesional skin was reduced more in NC/Nga mice that had been administered ultraviolet‐inactivated herpes simplex virus; their skin lesions improved after virus administration. We believe therefore that SOCS3 reduction downregulates Th2 and thus expression and/or levels of SOCS3 might provide a specific indication of the severity and/or improvement of AD and the shift from Th2 to Th1 or vice versa .…”
Section: Discussionmentioning
confidence: 85%
“…A recent report indicated that SOCS3 transgenic mice 5 show increased Th2 response. Data from experiments using the AD NC/Nga mouse model 11 clearly indicate strong SOCS3 mRNA expression and Th2 cellular response, with IL‐4‐ and p‐STAT6‐positive cellular infiltrates in the lesional skin of these mice, as has been found in human AD lesions 12 . SOCS3 expression may possibly be specific to atopic disorders and thus serve as an index of their severity 8 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…SOCS3 is a negative signal transducer specific for IL-12 as well as a signal transducer and activator of transcription 4 signaling, and thereby downregulates IFNγ production and Th1 immunity. SOCS3 was later found to be upregulated in an AE-like skin lesion in an AE model NC/Nga mouse [14]. IFNγ and IL-12 production by peripheral blood mononuclear cells increased significantly after successful treatment with topical glucocorticoids, while the production of IL-1, IL-4 and IL-13 was not significantly changed [15].…”
Section: Differentially Expressed Genes In T Cellsmentioning
confidence: 99%
“…The authors have experimented with animal models to scientifically support an observed clinical event. We have previously reported an improvement in AD-like lesions by UV-inactivated HSV 1 [55] in a murine atopy model (Nc/Nga mice), supporting a remarkable improvement in eczema lesions at the site of Kaposi's VE. On the other hand, Kawakami et al [56] described a relationship between defective NK cell activity and development of HSV 1-induced severe skin lesions (eczema herpeticum) in eczematous Nc/Nga mice.…”
Section: Immunoregulatory Events In Hsv Infectionmentioning
confidence: 58%